Evaluation of pre-operative sino-nasal outcome test- 22 scores as a predictor of outcome in patients undergoing functional endoscopic sinus surgery for chronic rhinosinusitis - Krishnaswami, Balasubramanian; Velayutham, Prabu; Pruthivirajan, Naveenkumar; Murugesan, Sathiyam; Murugesan, Ramkumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Numerous factors are to be considered when offering FESS as a treatment for patients with chronic rhinosinusitis (CRS) who have failed conservative medical treatment. The objective is to evaluate the sino-nasal outcome test (SNOT-22) and other patient demographic characteristics as predictors of postsurgical improvement in patients with CRS. Methods: Consecutive adult subjects presenting to the Otolaryngology clinics in a tertiary hospital, with refractory CRS that required surgery were included. Subjects were excluded if they did not complete both pre and post-operative SNOT-22 Questionnaire. Demographic and baseline measures, including allergic rhinitis, asthma and addiction status, Lund Kennedy endoscopic scores and Lund-Mackay computed tomography (CT) scoring were also obtained for each subject. Regression analyses were performed. Results: Fifty-one subjects met criteria and were included. These subjects showed a 55.4% overall improvement in postsurgical SNOT-22 evaluations. Multivariate regression analysis revealed that SNOT-22 items related to “runny nose,” “waking up at night”, “need to blow nose”, and “sneezing” were independent predictors of postsurgical SNOT-22 improvement (p<0.05, for all). Conclusions: ENT surgeons can utilize the SNOT-22 tool to predict the possibility of symptom improvement post FESS in patients with CRS.